Optimización Del Sistema De Ventilación De La Mina Charito, Compañía Minera Poderosa S.A. - Vergaray Valle, Roy Marlon (2017)
This research work entitled: "Optimization of the ventilation system of the Charito mine, Compañía Minera Poderosa", whose objective was to determine the most suitable design and ventilation method, to optimize the ventilation system of the Charito mine, Palca Project of Compañía Minera Poderosa SA. The Charito mine has blind fronts of work, so auxiliary ventilation is used. In the beginning, the ventilation method was used in the combination, with two fans of 10,000 CFM one installed as an aspirant and the other as impeller; the main problem being the prolonged ventilation time to evacuate the gases produced by blasting and the need for ventilation at other points of the mine, which are not considered in the initial system. For the present research project, a ventilation and calculations survey was carried out to determine the required flow; Two scenarios are presented, in the first where the required flow for people is evaluated and the second, for dilution of gases produced by blasting. Obtaining the flow required in the development stage of 8,534 CFM, taking into account the flow for personnel, is 2,966 CFM, whose value is less than the need for personnel. In addition, a performance comparison was made between a fan of 20,000 CFM and two of 10,000 CFM in total, connected to a 24 "fan, giving the best results of the 10,000 CFM fans trained. of 10 000 CFM each, taking into account that the angle of attack of the fan of 80 °, which will inject fresh air to the different work fronts in indoor mine through of ventilation sleeves of 24 "x100m, which meets the hypothesis.